2018
DOI: 10.1002/ghg.1831
|View full text |Cite
|
Sign up to set email alerts
|

Chemo‐mechanical behavior of clay‐rich fault gouges affected by CO2‐brine‐rock interactions

Abstract: The impact of long‐term CO2‐brine‐rock interactions on the frictional properties of faults is one of the main concerns when ensuring safe geological CO2 storage. Mineralogical changes may alter the frictional strength and seismogenic potential of pre‐existing faults bounding a storage complex. However, most of these reactions are too slow to be reproduced on laboratory timescales and can only be assessed using geochemical modeling. We combined modeling of CO2‐charged formation water and fault gouges (1–1000 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 61 publications
(150 reference statements)
0
11
1
Order By: Relevance
“…The initial Opalinus claystone contained a relatively high amount of quartz (44%), with major components including kaolinite (24%), calcite (16%), clinochlore (8%), and illite (8%). The composition found in this study differs from the composition of the larger formation found by, 21 which presents a much lower quartz (28%) and higher calcite content (25%).…”
Section: Undeformed Samples Opalinuscontrasting
confidence: 93%
See 1 more Smart Citation
“…The initial Opalinus claystone contained a relatively high amount of quartz (44%), with major components including kaolinite (24%), calcite (16%), clinochlore (8%), and illite (8%). The composition found in this study differs from the composition of the larger formation found by, 21 which presents a much lower quartz (28%) and higher calcite content (25%).…”
Section: Undeformed Samples Opalinuscontrasting
confidence: 93%
“…Fracturing not only may lead to an increase in porosity and permeability (facilitating CO 2 penetration), but also the shearing movement may lead to grain size reduction, causing the material to react faster. 21 The aim of this study was to evaluate and compare, via batch experiments and numerical modeling, the mineral alterations in sheared and undeformed samples of clay-rich caprock formations from Northern Europe after exposure to a CO 2 -rich brine. The caprock formations were selected based on their potential suitability to function as a seal for geological storage of CO 2 and likeliness to react within the experimental timeframe.…”
mentioning
confidence: 99%
“…When accounting also for the slip‐strengthening behavior of the possible composition of fault gouge in a clay formation (Orellana et al, ), it is evident that the canisters emplacement should stabilize normal faults in the host formation. Accordingly, rheological studies show that a rupture nucleating in the argillaceous formation would be likely aseismic because of intrinsic velocity‐strengthening behavior of clay‐rich fault material saturated with water (Bakker et al, ; Tembe et al, ). In contrast, deeper sections of a normal fault may be destabilized by the combined effect of thermoelastic and poroelastic stress and by pore pressure increase.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al, 2016). A limited number of experimental studies assess coupled chemical-mechanical behavior of caprock with CO 2 intrusion (Bakker et al, 2019;Ilgen et al, 2018;Spokas et al, 2018;Y. Zhang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Research on long‐term coupled chemical‐mechanical simulations in the caprock is very recent, with emphasis on coupled processes in GCS reservoirs and wellbores (Carroll et al, 2017; Iyer et al, 2020; R. Zhang et al, 2016). A limited number of experimental studies assess coupled chemical‐mechanical behavior of caprock with CO 2 intrusion (Bakker et al, 2019; Ilgen et al, 2018; Spokas et al, 2018; Y. Zhang et al, 2019). Most of these studies use carbonate‐rich caprock samples with excessive CO 2 partial pressure to observe obvious chemical alterations within limited experimental time.…”
Section: Introductionmentioning
confidence: 99%